A formação do médico: um debate à luz das diretrizes curriculares nacionais - Beltrame, Registila Libania (2006)
The premature specialization of the Medicine professional brought harm upon the holistic view of the human being by the physician and, as a consequence, upon the physician-patient relationship. The excessive use of technology and laboratory tests for diagnosis overloads the expenses for health care, without the corresponding increase in health production. Furthermore, medical activities practised in such manner would attend to interests of economic sectors that operate in the field of medicine, such as the pharmaceutical and medical and hospital equipment industries. The impossibility for this model of medical practice leading to the universal and equal access of the population to the health services has become a consensus in the world, which reinforces the need for curricular changes in the direction of forming a distinguished physician, that seeks to base the diagnosis on the patients history, anamnesis and a clinical examination with criteria. The change of paradigm in the medical education is considered necessary to promote the mould for humanist professionals, critic and reflective, whose priorities are the Primary Attention, promotion to Health, prevention of Diseases and that are capable of solving the cases of the prevailing diseases in the community. This professional profile is the recommended by the National Curricular Directives of the Medicine Graduation Course, published in 2001. However, the processes of curricular changes intended to the formation of the general doctor have been facing difficulties at schools. This work has as objective trying to understand the factors that make more difficult and those that make easier a process of curricular changes meant for the development of the general physician with the characteristics mentioned above. In the intention of placing the main problem of the research in context, are initially shown the relevance of this professional for the society, the basis of the medical education and its evolution, especially in our country, and the importance of the course programme and the medicine professor in the formation. Being characterized the relevant influence of the professors in the physician formation, they were chosen as subjects of the study, by two methods of data collecting: the questionnaires, of which answers from 32 professors were analysed by the Collective Subject Speech, and the analyses of the episodes observed in the school everyday life and considered relevant for the problem solution. Are shown as factors that make more difficult the implementation of a course programme which objectives to form a physician with solid general formation: lack of theoretic basis of the professors in the field of Education; teaching focused on specialities ambulatories and in hospitals, leading to the premature specialization; basic disciplines instructed by researchers, with non-humanized practices, detached from the clinic; attraction to the use of technologies (technology fetishism); specialization valued by professors in the form of a concealed curriculum; curricular fragmentation; lack of understanding of the social vision of the physician. Among the factors found which could assist in the process might be referred to: support from the Institution board of directors to the implementation process of the changes with tangible actions; the majority of professors to agreeing to the profile promoted by the National Curricular Directives; part of the professors to be formed in the own Institution, greatly compromised to the quality of the formed professional and to the democratic environment in which the discussions between professors occur, conducting to a greater conscience and sensitisation of them to promote the changes